A223 FRAILTY INCREASES THE RISK OF CIRRHOSIS DISEASE PROGRESSION, DEATH, AND HOSPITALIZATION IN CIRRHOSIS. (4th March 2021) - Wang, S; Xu, C; Whitlock, R; Taneja, S; Singh, S; Abraldes, J; Lai, J; Tandon, P
Abstract: Background: In cirrhosis, frailty is associated with increased risk of morbidity and mortality, including an increased risk of hospitalization. While frailty is established as a prognostic marker in cirrhosis, its impact on the progression of cirrhosis, especially in earlier stages of disease, remains unclear. Aims: To determine the relationship between frailty and risk of cirrhosis progression, mortality, and unplanned hospitalizations in patients with cirrhosis across the spectrum of disease. Methods: Adult patients with cirrhosis from two centers in North America and one in India were included in this retrospective review of prospectively collected data. Frailty was measured at baseline using the Liver Frailty Index (LFI), comprising grip strength, chair stands, and balance testing. Progression of cirrhosis was defined by an increase from one ordinal stage to the next using the D'Amico classification. Factors associated with progression, mortality, and hospitalizations were evaluated using multivariate competing risk regression models, with transplant as a competing risk. Results: In total, 822 patients with cirrhosis were included. The median MELD score was 15.5 ± 6.0. Of these patients, 201 (24.5%), 488 (59.4%), and 133 (16.2%) were classified as frail, pre-frail, and robust, respectively. Over a median follow up time of 1.2 years, 60 (7.3%) patients developed progression of cirrhosis, 187 (22.7%) died, 233 (28.3%) underwent liver transplantation, and 342 (41.6%) were alive without cirrhosis progression or transplant. Adjusting for age, sex, and MELD at baseline, being frail was associated with an increased risk of progression to the next cirrhosis stage or to death as compared to being robust (HR 2.47, 95% CI 1.63–3.76, p<0.001). As a continuous variable, every increase in the LFI by 0.1 unit increased the risk of decompensation or death by 1.05-fold (95% CI 1.04–1.07, p<0.001). Similarly, patients who were frail were more likely to be hospitalized as compared to patients who were robust (HR 2.88, 95% CI 2.08–3.98, p<0.001). Conclusions: Frailty was associated with an increased risk of cirrhosis progression or death, and hospitalization, independent of MELD at baseline. Future studies are needed to evaluate the possibility of slowing cirrhosis disease progression by reversing or preventing frailty. Funding Agencies: None